Reconstruction of the Limits of Teacher Discretion in Disciplinary Actions: Harmonization of the Child Protection Law and the Teacher and Lecturer Law - dahvit danang adi saputro adi saputro; Rezi Rezi; Muhamad Habib (Jurnal Cahaya Keadilan, 2026)
This study is motivated by the normative tension between teachers’ authority to impose disciplinary measures and legal provisions prohibiting violence against children, which creates legal uncertainty and increases the risk of criminalizing teachers in educational practice; the objective of this study is to formulate clear juridical boundaries for disciplinary actions so that they are not classified as criminal offenses and to develop a harmonization model between the Law on Teachers and Lecturers and the Child Protection Law; theoretically, this study contributes to the development of educational law, while practically it provides guidance for teachers, law enforcement officials, and policymakers; the method used is normative legal research with statutory and conceptual approaches, supported by qualitative analysis of legal materials; the findings indicate that lawful disciplinary actions must fulfill key parameters, namely educational purpose (animus educandi), proportionality, and respect for children’s dignity and rights, reinforced by the doctrine of in loco parentis as the basis for teachers acting as parental substitutes, while regulatory disharmony arises due to unclear operational limits; the study concludes that unclear limits of teachers’ discretion are the main source of legal uncertainty, thus requiring reconstruction through legal harmonization; therefore, it is recommended that legislation be revised to explicitly define these limits and that technical guidelines be established to ensure legal certainty and balanced protection for teachers and students.